2006
DOI: 10.1186/1471-2458-6-113
|View full text |Cite
|
Sign up to set email alerts
|

Screening chest radiography: results from a Greek cross-sectional survey

Abstract: Background: Public health authorities worldwide discourage the use of chest radiography as a screening modality, as the diagnostic performance of chest radiography does not justify its application for screening and may even be harmful, since people with false positive results may experience anxiety and concern. Despite the accumulated evidence, various reports suggest that primary care physicians throughout the world still prescribe chest radiography for screening. We therefore set out to index the use of ches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Except for the French and Italian studies, all of the included European studies used a measurement of social status. Moreover, a Greek study that assessed lung cancer screening through CXR used occupation as a social indicator [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for the French and Italian studies, all of the included European studies used a measurement of social status. Moreover, a Greek study that assessed lung cancer screening through CXR used occupation as a social indicator [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The definition of high-risk was 600 or more on the smoking index (average number of cigarettes smoked per day multiplied by the number of years of regular smoking) [ 20 ]. Other studies included current and past smokers as defined “[someone] who smokes or smoked cigarettes regularly” [ 23 ] or participants were categorized according to the number of daily cigarettes smoked (< 10, 10–20, 20–30, 30–40, > 40, no smokers) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, SESy-Europe project has used data coming from medical charts (questionnaires) of a Greek survey that aimed at the evaluation of Hellenic cancer preventive and screening practices (PACMeR_02 study). Details on PACMeR_02 study have been already reported [ 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…The lack of a centralized cancer screening and the opportunistic primary care practice in Greece have questionable results on cancer screening delivery (Panou et al 2004;Proiskos et al 2005;Kamposioras et al 2006Kamposioras et al , 2007Xilomenos et al 2006). However, there is no information on screening practices for Greek people diagnosed with diabetes.…”
Section: Introductionmentioning
confidence: 99%